Pemanfaatan Media Pembelajaran Interaktif Berbasis Aplikasi Articulate Storyline Pada Pembelajaran IPS Kelas V Sekolah Dasar - Aprilia Kurnia; Yesi Budiarti; Norma Yunaini (Proceedings Series on Social Sciences & Humanities, 2023)
Articulate Storyline application is one of the attractive learning media equipped with several supporting features such as audio visual so that the social studies learning process becomes more interesting. The use of facilities, infrastructure, and learning media is still not optimal. This is evidenced from the acquisition of data to educators and students that the use of class V interactive learning media at UPT SD Negeri 1 Sukoharjo III and UPT SD Negeri 2 Sukoharjo III is still not used maximally. This study aims to determine the feasibility and response of educators and students and determine the effectiveness of using interactive learning media in social studies learning. The research method used is Research and Development research using the Dick and Carey approach with 10 stages. Data sources are obtained based on interviews, documentation, and product trial results. The data analysis techniques used are validity, reliability, normality, homogeneity, paired simple T test, anova one way (one away). Based on the significant results of each group < a probability value (0.05) so that it can be concluded that interactive learning media based on articulate storyline applications are considered very interesting and effective.